2010
DOI: 10.1128/iai.00366-10
|View full text |Cite
|
Sign up to set email alerts
|

The K1 Capsular Polysaccharide of Acinetobacter baumannii Strain 307-0294 Is a Major Virulence Factor

Abstract: Acinetobacter baumannii is a pathogen of increasing medical importance with a propensity to be multidrug resistant, thereby making treatment challenging. Little is known of virulence traits in A. baumannii. To identify virulence factors and potential drug targets, random transposon (Tn) mutants derived from the A. baumannii strain AB307-0294 were screened to identify genes essential for growth in human ascites fluid in vitro, an inflammatory exudative fluid. These studies led to the identification of two genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
264
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(285 citation statements)
references
References 42 publications
12
264
0
5
Order By: Relevance
“…On all instruments the 5 most abundant precursor ions were selected and dynamic exclusion of 30 s enabled. MS resolution was set to 60,000 with an ACG target of 1 ϫ 10 6 , maximum fill time of 500 ms and a mass window of 600 to 2000 m/z. HCD fragmentation (normalized collision energy 40) was carried out with an ACG of 2 ϫ Glycopeptide Data Processing-The raw files were then processed within Proteome Discover version 1.3 (Thermo Scientific) to generate mgf files and searched using Sequest against a composite FASTA database of strain SDF, ATCC17978, and AYE (NCBI accession: NC_010400.1, NC_009085.1 and NC_010410.1 respectively, obtained from NCBI on 10/07/2012).…”
Section: Methodsmentioning
confidence: 99%
“…On all instruments the 5 most abundant precursor ions were selected and dynamic exclusion of 30 s enabled. MS resolution was set to 60,000 with an ACG target of 1 ϫ 10 6 , maximum fill time of 500 ms and a mass window of 600 to 2000 m/z. HCD fragmentation (normalized collision energy 40) was carried out with an ACG of 2 ϫ Glycopeptide Data Processing-The raw files were then processed within Proteome Discover version 1.3 (Thermo Scientific) to generate mgf files and searched using Sequest against a composite FASTA database of strain SDF, ATCC17978, and AYE (NCBI accession: NC_010400.1, NC_009085.1 and NC_010410.1 respectively, obtained from NCBI on 10/07/2012).…”
Section: Methodsmentioning
confidence: 99%
“…The active protection of the CPS enables A. baumannii to avoid bactericidal activity of the complement. The authors also suggested that the CPS protection against the effects of phagocytes or antimicrobial peptides requires further studies [26]. AbOmpA is considered to be one of the best-characterised A. baumannii virulence factors.…”
Section: Virulence Factorsmentioning
confidence: 99%
“…A pilot study assessing A. baumannii infection of bone in a rat model has also been performed (45). Virulence factors that have been identified using this approach include penicillinbinding protein 7/8 (20), a glycosyltransferase (LpsB) involved in LPS biosynthesis (23), and genes (ptk and epsA) important for capsule formation (22). Phospholipase D was shown to be important for growth in human serum and for epithelial cell invasion, but in the murine pneumonia model, similar bacterial burdens and histopathology were identified (24).…”
Section: Use Of In Vivo Mammalian Model Systems To Study a Baumanniimentioning
confidence: 99%